Profile Of Leishmaniasis In Central Kerala - Criton S; Devi K; Sridevi P K; Asokan P U (Wolters Kluwer Medknow Publications, 1997)
Leishmaniasis is a group of diseases caused by several species of the genus leishmania. It is not prevalent in Kerala even though there are a few case reports. Recently, a focus of indigenous leishmaniasis is located in the north- east part of Kerala. We are also reporting probably indigenous cases along with those contracted from Middle- east countries.